Cognitive Behavior Therapy (CBT) Counseling in Addressing Verbally Aggressive Behavior of Students in Junior High Schools - Angelina Ekaputri; Anisatin Jidayah; Arif Ainur Rofiq (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
This study aims to determine the application of Cognitive Behavioral Therapy (CBT) counseling services in addressing verbally aggressive behavior in a student with the initials MDW at MTsN 2 Lamongan. This study used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed through the case study stages including problem identification, diagnosis, prognosis, treatment, evaluation, and follow-up. The results showed that CBT counseling services were effective in helping reduce verbally aggressive behavior in students after being given treatment in the form of initial assessment and diagnosis, report preparation, commitment making, behavior modification, and evaluation and follow-up. Positive changes in the MDW research subject were characterized by changes in cognitive, emotional control, and social behavior as seen through the ability to manage emotions, as well as being able to communicate more assertively and constructively in social situations. Thus, CBT is an effective approach in counseling services to address verbally aggressive behavior in students in the school environment.